2007
DOI: 10.1186/1477-3155-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Self assembly of amphiphilic C60 fullerene derivatives into nanoscale supramolecular structures

Abstract: Background: The amphiphilic fullerene monomer (AF-1) consists of a "buckyball" cage to which a Newkome-like dendrimer unit and five lipophilic C 12 chains positioned octahedrally to the dendrimer unit are attached. In this study, we report a novel fullerene-based liposome termed 'buckysome' that is water soluble and forms stable spherical nanometer sized vesicles. Cryogenic electron microscopy (Cryo-EM), transmission electron microscopy (TEM), and dynamic light scattering (DLS) studies were used to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…PBMCs were prepared as described above, pretreated with rILYd4 (20 µg/ml) at 37°C for 15 min, suspended in GVB ++ , and exposed to the same patient's serum or plasma (50%) as a source of complement. PBMC lysis was assessed by the release of lactate dehydrogenase measured with the CytoTox-ONE kit according to the manufacturers' instructions (Promega, Madison, WI) (21). The fluorescent signal was recorded at 560/590 nm using Fluostar Optima (BMG Labtech, Cary, NC).…”
Section: Assessment Of the Nonspecific Cytolytic Effect Of Rilyd4 On mentioning
confidence: 99%
“…PBMCs were prepared as described above, pretreated with rILYd4 (20 µg/ml) at 37°C for 15 min, suspended in GVB ++ , and exposed to the same patient's serum or plasma (50%) as a source of complement. PBMC lysis was assessed by the release of lactate dehydrogenase measured with the CytoTox-ONE kit according to the manufacturers' instructions (Promega, Madison, WI) (21). The fluorescent signal was recorded at 560/590 nm using Fluostar Optima (BMG Labtech, Cary, NC).…”
Section: Assessment Of the Nonspecific Cytolytic Effect Of Rilyd4 On mentioning
confidence: 99%
“…In this connection, mention should be made of a dendrimer derivative of C 60 , AF-1, where the fullerene core is modified with a Newkome-like dendrimer unit containing 18 carboxyl groups and five dodecyl malonate residues which are positioned octahedrally to the dendrimer. 308 This compound can self-assemble to form spherical nanostructures referred to as`buckysomes' } of size 100 ± 200 nm in water. 309 Empty buckysomes are not cytotoxic.…”
Section: Iii3 Biomedical Applicationsmentioning
confidence: 99%
“…[13][14][15] The "amphifullerene" compounds, which are based on a C 60 core, contain both hydrophobic (water-insoluble) and These buckysomes are the first reported instance of a watersoluble fullerene that is capable of forming a vesicle through instantaneous self-assembly. Amphiphilic fullerene-1 (AF-1) is one such novel functionalized fullerene which can selfassemble into either a hydrophilic vesicle with a hollow interior 38 or a solid spherical nanostructure with a dense hydrophobic interior. 39 The fullerene monomer AF-1, consists of a "buckyball" cage to which a Newkome-like dendrimer unit and ten hydrophobic C 12 chains positioned octahedrally to the dendrimer are attached (Figure 2).…”
Section: List Of Functionalized Fullerenesmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37] In addition, this review will emphasize the clinical applications of a certain group of fullerenes functionalized with amphiphilic and dendritic groups by Hirsch and colleagues. [13][14][15] Our research group has been investigating the use of amphiphilic fullerenes 38,39 and dendritic fullerenes for drug delivery and ROS quenching, respectively. We have successfully demonstrated that amphiphilic fullerenes are capable of forming spherical vesicles in the order of 100-150 nm termed "buckysomes."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation